PERKEMBANGAN TEKNOLOGI DALAM PROSES PERCETAKAN 3 DIMENSI DAN APLIKASINYA - setiyo adi nugroho; Arie Atwa Magriyanti (STEKOM PRESS, 2020)
Developing of prototype now are became easier with the existence of 3 d printer, now is common known as rapid prototyping method. There are many different method on 3d printing depend on material used for printing. The wide range of material that can be print using 3d printer such as metal to plastic even ceramic. The rapid prototyping using 3d printer have various advantage compare to traditional prototyping. The development of 3d printing makes it not only for prototyping but can be a small batch manufacture, where economic scale of production cannot be reach with traditional production. The fast development of computer and internet technology have big impact on the 3d printer development, before the development of reprap 3d printing was only knew by industrialist and manufacturer. After reprap born, 3d printer is became more common to personal user. People can have their 3d printer at home. People can design their own product using CAD software and send it to 3d printer, or send it via internet to print by 3d printing company. Even there ara lot of advantages of 3D printer development , there is some disadvantages of 3d printer, especially on regulation.